Sistem Informasi Geografis Pemetaan Bangunan Kota Pekanbaru Berbasis Web - Muhammad Ihsanul Fikri; Siti Ramadhani; Tomi Z (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
Pekanbaru City Public Works and Spatial Planning Office in conveying building information that will display the location of the building along with detailed information about the location of the building so that it is easier to see which buildings are lacking building information so that the Public Works and Spatial Planning Office can pay more attention to buildings. . So with the construction of the web-based Geographic Information System for Building Mapping, it is intended that this application can provide convenience to users in viewing information about building information and the location of the building location they want to know in the city of Pekanbaru. In designing this system, an analysis is carried out using the Unified Modeling Language (UML) model which includes Use Case Diagrams, Activity Diagrams, Sequence Diagrams, Entity Relationship Diagrams, and Data Flow Diagrams. The Mapping Geographic Information System that has been built is able to provide convenience to users.